(untitled) (Bangladesh Medical Journal Khulna, 2020)
Background: Different bacterial enteropathogens are responsible for diarrhoea in children less than 5 years of age in Bangladesh. This study aimed to determine the antimicrobial sensitivity pattern of diarrhoeal pathogens that is necessary to know for the specific management of acute bacterial diarrhoea. Objectives: To find out the bacterial enteropathogens causing diarrhoea and their antimicrobial sensitivity pattern in under 5 children. Methodology: This was an observational cross sectional study carried out at Microbiology Department of Sir Salimullah Medical College, Dhaka. A total of 217 diarrhoeal patients 0-5 years age, attending Pediatric unit of Sir Salimullah Medical College and Mitford Hospital. Dhaka and Dhaka Shishu Hospital, Dhaka during the period of July, 2015 to June, 2016, were enrolled in the study. For isolation of the common enteric bacteria, diarrhoeal stools were cultured on MacConkey agar media and for Campylobacter spp, diarrhoeal stools were cultured on selective Modified Campy BAP media and nonselective Blood agar media with membrane filter. Positive culture was confirmed by Gram stain morphology and standard biochemical tests. Antimicrobial susceptibility test were used to identify the bacterial sensitivity pattern in the isolates. Results: Out of 217 diarrhoeal stools, bacteria was isolated from 97 (44.70%) patients by culture. Among 97 culture positive cases Eschericha coli (51- 52.58%), Campylobacter spp. (23-23.71%), Shigella spp. (15-15.46%) and Salmonella spp. (8-8.25%) were isolated. Mecillinam is the most sensitive drug for Escherichia coli, Campylobacter spp., Shigella spp. and Salmonella spp. Among the other antimicrobials, Campylabacter spp. were sensitive to azithromycin, erythromycin and nitrofurantoin. Escherichia coli were sensitive to nitrofurantoin, gentamicin and azithromycin. Shigella spp. were sensitive to ceftriaxone, ciprofloxacin and nitrofurantoin and Salmonella spp. were sensitive to ceftriaxone, cotrimoxazole and gentamicin. Conclusion: Mecillinam and nitrofurantoin were highly effective against bacteria causing diarrhoea in children. Bang Med J (Khulna) 2019; 52 : 35-39